2015
DOI: 10.1103/physrevb.91.214512
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for two distinct superconducting phases inEuBiS2Funder pressure

Abstract: We present a pressure study of the electrical resistivity, ac magnetic susceptibility and powder x-ray diffraction (XRD) of the recently discovered BiS2-based superconductor EuBiS2F. At ambient pressure, EuBiS2F shows an anomaly in the resistivity at around T0 ≈ 280 K and a superconducting transition at Tc ≈ 0.3 K. Upon applying hydrostatic pressure, there is little change in T0 but the amplitude of the resistive anomaly is suppressed, whereas there is a dramatic enhancement of Tc from 0.3 K to about 8.6 K at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
30
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 21 publications
12
30
0
Order By: Relevance
“…Enhancement of Tc of Eu-1112 (Tc = 8.6 K at 1.86 GPa) and Eu-3244 (Tc = 10 K at 2 GPa) has been reported by chemical and external pressure effects [28][29][30][31] .…”
Section: Introductionmentioning
confidence: 98%
“…Enhancement of Tc of Eu-1112 (Tc = 8.6 K at 1.86 GPa) and Eu-3244 (Tc = 10 K at 2 GPa) has been reported by chemical and external pressure effects [28][29][30][31] .…”
Section: Introductionmentioning
confidence: 98%
“…12,19,20 On the other hand, LaO 0.5 F 0.5 BiS 2 (AP), which has a low T c , undergoes a structural phase transition from tetragonal to monoclinic at a pressure of 0.7 GPa, and T c is enhanced to 10.7 K. 21 Similar abrupt increases in T c were also observed in the compounds LnO 0.5 F 0.5 BiS 2 (Ln = Ce, Pr, Nd), LaO 0.5 F 0.5 BiSe 2 , EuBiS 2 F and Eu 3 Bi 2 S 4 F 4 under pressure. [22][23][24][25][26] A gradual increase in T c up to 5.4 K was observed at ambient pressure in La 1−x Sm x O 0.5 F 0.5 BiS 2 with increasing Sm concentration until the solubility limit near x = 0.8. 27 The lattice parameter a in La 0.2 Sm 0.8 O 0.5 F 0.5 BiS 2 is significantly smaller compared with other BiS 2 based compounds; however, further optimization of superconductivity in this system is prevented by the presence of a solubility limit.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the ways of effectively increasing Tc of BiS 2 -based superconductors are as follows: (1) The Tc of samples prepared using a conventional solid state reaction -such samples are called as-grown samples in this articlecan be increased by applying high pressure [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Asgrown LaO 1−x FxBiS 2 shows superconductivity at approximately 3 K at ambient pressure for the optimal x value.…”
Section: Effects Of External Pressurementioning
confidence: 99%
“…This phenomenon has been demonstrated using three above-mentioned methods (i.e., (1)- (3)) suggests that the superconductivity of BiS 2 -based materials is sensitive to high pressure and that their Tc value can be increased by optimizing their crystal structure. Indeed, high-pressure X-ray diffraction analyses of LaO 0.5 F 0.5 BiS 2 and EuFBiS 2 have revealed that their crystal structure transforms from tetragonal to monoclinic with space group P2 1 /m symmetry under high pressure [32,43]. This result suggests that the monoclinic structure is preferable for increasing the Tc value and that the increase in Tc owing to high-pressure annealing is probably related to the local distortion of the crystal structure into a monoclinic or other type of low-symmetry structure.…”
Section: Effects Of External Pressurementioning
confidence: 99%